TOWARD A THEOLOGY OF CHRISTIAN MINORITY IN INDIAN SCENARIO TODAY: Indian Theological Association (ITA) Statement 2016 - Association, Indian Theological (Asian Horizons, 2016)
We, the members of the Indian Theological Association (ITA), gathered at Montfort Spirituality Centre, Bengaluru for the 39th Annual Meeting cum Seminar during 27-30 April 2016, reflected on the theme, “Toward a Theology of Christian Minority in the Indian Scenario Today” and articulated our theological response to the precarious situation of the religious minorities in general and the Christian minority in particular. It is a fact that minorities in any situation can feel threatened and insecure because they feel powerless before the might of the majority. But in the present Indian situation the vulnerability of the religious minorities has worsened because of the policies and programmes as well as the covert and overt actions of the present BJP government which is guided by the Hindutva ideology of the RSS and its affiliates for whom Muslims and Christians are a threat to their establishment of the Hindu cultural nationalism.